PREVENTING VIOLENCE: GENERATING AND USING THE EVIDENCE. (7th October 2012) - Butchart, A
Abstract : WHO, along with other United Nations organisations and international agencies working to strengthen violence prevention at national and local levels, advocates an evidence-based approach to prevent the problem of violence. The case for evidence-based approaches is an ethical one—to do as much good as possible with available resources. Without using an evidence-based approach, well-intentioned policymakers and practitioners can squander scare resources on policies and programmes that are at best ineffective and in some instances actively harmful. Drawing on reviews of the scientific literature, and using the Liverpool John Moores University—WHO online violence prevention database as an indicator of all published violence prevention outcome evaluation studies, this presentation has three aims. The first aim is to map the distribution of outcome evaluation studies by type of violence (ie, child maltreatment; youth violence; intimate partner violence; sexual violence; elder maltreatment, and self-directed violence); level of intervention (ie, individual, family, community, societal), and WHO geographical region. The second aim is to map progress in implementing the four stages of the public health approach to violence prevention (ie, problem description, risk factor identification, intervention evaluation, and scaling up) by country income level and type of violence. The third aim is to suggest priority actions for generating and using scientific evidence for the prevention of violence.